Mowa niezależna w przekazie medialnym a podstawowe funkcje informacji dziennikarskiej (część 3) - Grzelka, Monika; Kula, Agnieszka (Wydawnictwo „Poznańskie Studia Polonistyczne” i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
This article is a part of research project that focuses on citations in media coverage in Poland after 1989; two earlier installments of the article have been included in earlier publications of “Poznańskie Studia Polonistyczne”. Part Three provides a discussion on and characteristics of the category of the average man in the street, ordinary people whose utterances are increasingly included in the journalistic narration. Taking the notion of everyday life, with which the demand for an ordinary man in the media is closely linked, as a starting point in the discussion, the authors proceed to characterize citations, along with their explanatory attributions, indicate their textual functions and analyse the categories that are revealed within the process: anonymity, transparency and singularity.
Keywords: information; informality; citation; media coverage; indirect speech; quotation